2006
DOI: 10.1111/j.1365-313x.2005.02641.x
|View full text |Cite
|
Sign up to set email alerts
|

The WAG1 and WAG2 protein kinases negatively regulate root waving in Arabidopsis

Abstract: SummaryThe WAG1 and WAG2 genes of Arabidopsis thaliana encode protein-serine/threonine kinases that are closely related to PINOID. In order to determine what roles WAG1 and WAG2 play in seedling development, we used a reverse genetics approach to study the wag1, wag2 and wag1/wag2 mutant phenotypes for clues. Although the wag mutants do not contain detectable amounts of the corresponding mRNA, they are wild type in most respects. However, wag1/wag2 double mutants exhibit a pronounced wavy root phenotype when g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
96
0
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(101 citation statements)
references
References 56 publications
3
96
0
2
Order By: Relevance
“…To further assay the effect of PIF4 and/or PIF5 on auxin-related processes, we examined polar auxin transport. In our microarray data, we found that PIF4 and/or PIF5 up-regulate some polar auxin transportrelated genes such as PIN-FORMED3 (Friml et al, 2002), ATHB2 (Steindler et al, 1999), and WAG2 (Santner and Watson, 2006;Supplemental Table S5; Supplemental Fig. S2).…”
Section: Pif4 and Pif5 Modulate Auxin Signalingmentioning
confidence: 93%
“…To further assay the effect of PIF4 and/or PIF5 on auxin-related processes, we examined polar auxin transport. In our microarray data, we found that PIF4 and/or PIF5 up-regulate some polar auxin transportrelated genes such as PIN-FORMED3 (Friml et al, 2002), ATHB2 (Steindler et al, 1999), and WAG2 (Santner and Watson, 2006;Supplemental Table S5; Supplemental Fig. S2).…”
Section: Pif4 and Pif5 Modulate Auxin Signalingmentioning
confidence: 93%
“…7). Recently, Santner and Watson (24) suggested that gravitropism is not required for the wavy growth response. This conclusion is in agreement with the observation that miz1 roots show a modified wavy growth response but their gravitropic response is identical to that of WT roots.…”
Section: Resultsmentioning
confidence: 99%
“…Baster et al (2013) suggested that posttranslational regulation of PIN2 could lead to its proteasomal and vacuolar lytic degradation. The polar localization of PIN2 is regulated via phosphorylation by PINOID (PID) and its related protein kinases WAG1 and WAG2 that in turn are antagonized by protein phosphatase 2AA (Michniewicz et al, 2007;Adamowski and Friml, 2015;Santner and Watson, 2006). It is not shown here but conceivable that a similar regulatory mechanism targets PIN2 for degradation.…”
Section: Hypoxia Increases Auxin Activity At the Root Tipmentioning
confidence: 99%